Upaya Meningkatkan Keterampilan Menulis Procedure Text Mata Pelajaran Bahasa Inggris melalui Model Mind Mapping Siswa Kelas IX.B SMP Negeri 6 Mataram - Windrawati, Ni Ketut Ayu (Lembaga Yasin AlSys, 2023)
The objectives of this classroom action research were: (1) To find out the application of the mind mapping model to improve the ability to write Procedure Text for English subjects for Class IX.B SMP Negeri 6 Mataram Academic Year 20222/2023; (2) To find out the increase in the ability to write Procedure Text for English subjects through the application of the Mind Mapping model for Class IX.B students of SMP Negeri 6 Mataram in the Academic Year 2022/2023. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research was students of Class IX.B SMP Negeri 6 Mataram with a total of 38 students consisting of 16 boys and 22 girls. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. The results of the study proved that there was an increase in the English subject's procedure text writing skills as follows: The learning achievements of students in English subjects were as follows: the average value before the action was 85.74, in the first cycle 85.82 was obtained and the average value was average in cycle II obtained 88.47. The same thing happened to the increase in the number of students who reached the minimum completion limit (> 80), namely before the action 26 students (68.42%), who completed in cycle I were 31 students (81.58%) and in cycle II increased to 38 students (100%).